SPEECH ACT FOUND IN RAYA AND THE LAST DRAGON MOVIE - Ires Putri Hartawati Ningrum; Fenny Thresia; Bambang Eko Siagiyanto (Journal of English Education and Enterpreneurship (JEEP), 2022)
This study aimed to find types and the most dominant speech act of illocutionary acts found in Raya and the Last Dragon movie. This study utilized a descriptive qualitative method. Primary and secondary data were collected to find the answers of the problem. As in the primary data, the researcher used the movie and the movie script and in the secondary data, the researcher used a related literature or research papers to support the study. The data were analyzed in four phases; data management, data reduction, data display, and verification. The findings revealed that the movie utilized all of the illocutionary acts as many as, 92 utterances comprises 4 are declarative, 13 are representative, 27 are expressive, 32 are directive, and 15 are commissive. The result also revealed that directive speech act to be the most dominant utterance spoken by the characters in the movie and declarative speech act to be the least utterance spoken.